Advising Depression Patients to Reduce Alcohol and Drug Use: Factors Associated With Provider Intervention in Outpatient Psychiatry - Satre, Derek D. (Am J Addict, 2014)
BACKGROUND AND OBJECTIVES: Mental health clinicians have an important opportunity to help depression patients reduce co-occurring alcohol and drug use. This study examined demographic and clinical patient characteristics and service factors associated with receiving a recommendation to reduce alcohol and drug use from providers in a university-based outpatient psychiatry clinic. METHODS: The sample consisted of 97 participants ages 18 and older who reported hazardous drinking (≥3 drinks/occasion), illegal drug use (primarily cannabis) or misuse of prescription drugs, and who scored ≥15 on the Beck Depression Inventory-II (BDI-II). Participants were interviewed at intake and 6 months. RESULTS: At 6-month telephone interview, 30% of participants reported that a clinic provider had recommended that they reduce alcohol or drug use. In logistic regression, factors associated with receiving advice to reduce use included greater number of drinks consumed in the 30 days prior to intake (p = .035); and greater depression severity on the BDI-II (p = .096) and hazardous drinking at 6 months (p = .05). CONCLUSIONS AND SCIENTIFIC SIGNIFICANCE: While participants with greater alcohol intake and depression symptom severity were more likely to receive advice to reduce use, the low overall rate of recommendation to reduce use highlights the need to improve alcohol and drug use intervention among depression patients, and potentially to address alcohol and drug training and treatment implementation issues among mental health providers.